From Burnout to Balance : How to reclaim your life & improve your health - Griffey, Harriet (London : Hardie Grant Books, 2020)
Harriet Griffey helps readers to reclaim their life by recognising their own signs of stress, managing these and avoiding their escalation through positive lifestyle changes, and ensuring basic self-care measures every day - adequate sleep, regular nutritious meals, exercise and relaxation - to keep body and mind resilient, all helps.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Burn out (Psychology) -- Treatment; Stress management